Review Studi Difraksi Fresnel Menggunakan Celah Bentuk Lingkaran - Rosyidah, Arinar; Marhaendrajaya, Indras; Firduasi, K. Sofjan (BERKALA FISIKA, 2008)
The Fresnel Diffraction has been reviewed to measure the wavelenght of monochromatic light sources. The change of circle fringe’s number is obtained by the change of the distance between source and slits, and the change of fringe’s radius. We used here the diode green pointer laser and red pointer laser as light sources with 1 mW in power. From the measurement, we obtained that the wavelenght of green laser and red pointer laser are still in the range of literature values. Key words: Fresnel diffraction, Fresnel zone.